2022
DOI: 10.1177/14713012221126288
|View full text |Cite
|
Sign up to set email alerts
|

“An animated socialization without substance:” experiences of persons living with dementia through the COVID-19 pandemic

Abstract: Background Like so many others, persons living with dementia have been greatly impacted by the COVID-19 pandemic. A Stakeholder Advisory Council set a research priority to learn more about the experiences of families living with dementia during COVID-19. Methods This study was conducted using a multi-method design. Online surveys were completed by 27 persons living with dementia to rate the impact of COVID-19 on their health and healthcare. Additionally, interviews (n = 3) and two focus groups were conducted v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A study found that people who spent most of their time during COVID-19 in the home office and thus in video conferences slipped into a comparison with the “good old days” and that technical problems also led to a certain fatigue. Nevertheless, PLWDs describing that COVID-19 impacted on their quality of life, also used technology for socialization and support ( Glassner et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A study found that people who spent most of their time during COVID-19 in the home office and thus in video conferences slipped into a comparison with the “good old days” and that technical problems also led to a certain fatigue. Nevertheless, PLWDs describing that COVID-19 impacted on their quality of life, also used technology for socialization and support ( Glassner et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%